2021
DOI: 10.3390/ijms22136791
|View full text |Cite
|
Sign up to set email alerts
|

Using RNA-Sequencing Data to Examine Tissue-Specific Garlic Microbiomes

Abstract: Garlic (Allium sativum) is a perennial bulbous plant. Due to its clonal propagation, various diseases threaten the yield and quality of garlic. In this study, we conducted in silico analysis to identify microorganisms, bacteria, fungi, and viruses in six different tissues using garlic RNA-sequencing data. The number of identified microbial species was the highest in inflorescences, followed by flowers and bulb cloves. With the Kraken2 tool, 57% of identified microbial reads were assigned to bacteria and 41% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Generally, the relative content was bacteria > fungi > protozoa > viruses, but in maize kernels and roots, the relative content of fungi exceeded that of bacteria. In general, numerous studies have shown that bacteria are the predominant of all microorganisms [45][46][47], but the results of the new analysis strategy showed the composition of various types of microorganisms, from which it can be seen that eukaryotic microorganisms, including fungi and protozoa, sometimes dominate in specific tissues. In addition, protozoa are generally not a hot spot for research on plant endophytic microorganisms; however, in this study, we note that the relative content of protozoa should not be neglected, as they may also play an important role in promoting plant growth and other aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the relative content was bacteria > fungi > protozoa > viruses, but in maize kernels and roots, the relative content of fungi exceeded that of bacteria. In general, numerous studies have shown that bacteria are the predominant of all microorganisms [45][46][47], but the results of the new analysis strategy showed the composition of various types of microorganisms, from which it can be seen that eukaryotic microorganisms, including fungi and protozoa, sometimes dominate in specific tissues. In addition, protozoa are generally not a hot spot for research on plant endophytic microorganisms; however, in this study, we note that the relative content of protozoa should not be neglected, as they may also play an important role in promoting plant growth and other aspects.…”
Section: Discussionmentioning
confidence: 99%
“…An example supporting this thesis are higher values of all alpha biodiversity indicators in variants containing garlic and the increase in the share of Pseudomonaceae and Enterobacteriaceae families. These taxa were claimed as dominant in the microbiota of garlic bulb cloves [ 35 ]. Targeted changes in taxonomic structure and thus changes in overall metabolic metapopulation potential probably affect the formic acid fermentation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These new techniques provides more information about the composition of the bacterial community than traditional cloning and sequencing methods. Among them, Kraken2 has been found to be very reliable in microbial identification in a large number of studies, especially in microbiome studies based on RNA sequencing data 19 . Poore has been provided a valuable and feasible approach to discovering unique microbial information by analyzing genome-wide and transcriptomic data from blood and tissues of cancer patients 20 .…”
Section: Introductionmentioning
confidence: 99%